I'Jaz Concept and its Relationship with Miracles in the Qur'an - Gunawan, Gun Gun; Riyani, Irma (UIN Sunan Gunung Djati Bandung, 2023)
I'jaz is the ability to subdue and show himself above others. When this term was applied to the Qur'an, the holy book brought by the Prophet was able to subdue all the writings that ever existed, while also crowning the Qur'an as a miracle as well as the most noble and undeniable book. The miracles of the Qur'an cannot be matched. This is manifested in aspects of the beauty of language, the stories contained in it, in addition to monotheism, the rules of the Shari'a, and so on, as well as scientific information that is extraordinarily complete when examined in depth. To appreciate the miracles of the Qur'an, every Muslim should fulfill the rights of the Qur'an by reading, memorizing, studying, analyzing and applying it in daily life as a guide for those who are pious.